1)tg a * ctg a= 2)выразить sin^2a через cos^2a 3)cos^a-1= 4)1-sin^2a= 5)1+tg^2a= 6)sin^2a-1 7)tg a через ctg a 8)cos a через ctg a

1)tg a * ctg a= 2)выразить sin^2a через cos^2a 3)cos^a-1= 4)1-sin^2a= 5)1+tg^2a= 6)sin^2a-1 7)tg a через ctg a 8)cos a через ctg a
Гость
Ответ(ы) на вопрос:
Гость
1) tg(α)*ctg(α)=sin(α)/cos(α)*cos(α)/sin(α)=1 2) sin²(α)=1-cos²(α) 3) cos²(α)-1=cos²(α)-(sin²(α)+cos²(α))=-sin²(α) 4) 1-sin²(α)=cos²(α) 5) 1+tg²(α)=1+sin²(α)/cos²(α)=(cos²(α)+sin²(α))/cos²(α)=1/cos²(α) 6) sin²(α)-1=sin²(α)-(sin²(α)+cos²(α))=-cos²(α) 7) tg(α)=sin(α)/cos(α)=1/(cos(α)/sin(α))=1/ctg(α) 8) ctg(α)=cos(α)/sin(α), cos(α)=ctg(α)*sin(α). А так как sin(α)=√(1/(1+ctg²(α)), то cos(α)=√(ctg²(α)/(1+ctg²(α)))   
Не нашли ответ?
Ответить на вопрос
Похожие вопросы